Tinjauan Yuridis Terhadap Atlet Yang Tidak Mendapatkan Hari Tua Berdasarkan Peraturan Presiden Nomor 4 Tahun 2014 Tentang Pemberian Penghargaan Olahrga Dalam Perspektif Hak Asasi Manusia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
In the field of sports in Indonesia, the law has not played a full role. So far, the field of sports is only regulated by statutory regulations under partial laws or has not completely regulated all aspects of national sports, and has not reflected an orderly legal order in the field of sports. The achievements of national sports in the world arena are still far from satisfactory. Overall, Indonesia has not been able to compete in the international arena. It could be that the cause is that the welfare of athletes in Indonesia is not fully guaranteed. On the other hand, government support through its performance greatly influences the spirit of achievement of athletes to compete in world events. And this is in accordance with the statement of the former minister of youth and sports, Imam Nahrawi, wanting an athlete law, one of which is to guarantee the welfare of former athletes in their old age.This legal research is normative legal research. Normative legal research is legal research conducted by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. This research examines the subject matter according to the scope and scope of the study. Identification of problems through a statute approach is carried out by examining statutory regulations and regulations related to the legal issues under study. In this study, the authors conducted research on the Principles of Legal Principles. This study examines the juridical review of athletes who do not get a guarantee in old age based on presidential regulation number 44 of 2014 concerning the award of sports from a human rights perspective.The results of this study are expected to guarantee the old age rights for athletes according to the legislation based on Presidential Regulation Number 44 of 2014 concerning the Giving of Sports Awards and to know what are the limitations of the athlete's guarantee regarding the Giving of Sports Awards. And what rights will be received by athletes should be included in the law and the state's responsibility for athletes should be realized.Keywords: Implementation - Regional Regulation - Persons with Disabilities